From the guest editors - Lewis, Martin; Magidimisha, Hangwelani Hope (Town and Regional Planning, 2019)
The land issue is still making waves across Southern Africa, with South Africa being the latest focus of dispute. An article, featured in the Daily Maverick on 29 May 2019, indicates that “Land reform is a broad social challenge that requires the commitment of every South African to ensure the sustainability and prosperity of an inclusive South African economy. The land question is not only an agricultural land problem, but it also relates to urban and peri-urban land” (Kirsten & Vink, 2019: n.p.).